2015
DOI: 10.1136/heartjnl-2015-308624
|View full text |Cite
|
Sign up to set email alerts
|

Pregnancy course and outcomes in women with arrhythmogenic right ventricular cardiomyopathy

Abstract: ObjectivesTo characterise pregnancy course and outcomes in women with arrhythmogenic right ventricular dysplasia/cardiomyopathy (ARVD/C).MethodsFrom a combined Johns Hopkins/Dutch ARVD/C registry, we identified 26 women affected with ARVD/C (by 2010 Task Force Criteria) during 39 singleton pregnancies >13 weeks (1–4 per woman). Cardiac symptoms, treatment and episodes of sustained ventricular arrhythmias (VAs) and heart failure (HF) ≥ Class C were characterised. Obstetric outcomes were ascertained. Incidence o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
36
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
2
1

Relationship

2
8

Authors

Journals

citations
Cited by 52 publications
(38 citation statements)
references
References 25 publications
(44 reference statements)
2
36
0
Order By: Relevance
“…Atrial fibrillation may reflect electrical instability and has been associated with life-threatening arrhythmic events 66 . Risk of ventricular arrhythmia does not seem to significantly increase during pregnancy 133 . Unwillingness to restrict exercise has also been associated with higher risk of ventricular arrhythmia, 17 , 62 The absence of risk factors confers a low risk of sudden death (<1% per year) and ICD is not indicated 1 …”
Section: Management Of Arrhythmogenic Right Ventricular Dysplasia/carmentioning
confidence: 99%
“…Atrial fibrillation may reflect electrical instability and has been associated with life-threatening arrhythmic events 66 . Risk of ventricular arrhythmia does not seem to significantly increase during pregnancy 133 . Unwillingness to restrict exercise has also been associated with higher risk of ventricular arrhythmia, 17 , 62 The absence of risk factors confers a low risk of sudden death (<1% per year) and ICD is not indicated 1 …”
Section: Management Of Arrhythmogenic Right Ventricular Dysplasia/carmentioning
confidence: 99%
“…As the disease is frequently diagnosed in women of childbearing age, 10 data regarding the effect of pregnancy on disease progression is needed to improve patient advice 11 . However, such data are sparse with only two published studies on the effect of pregnancy in 6 and 26 women with AC, 12 , 13 respectively, in addition to case reports 14 , 15 . We aimed to investigate the relation between parity and cardiac structure, function, arrhythmias, and clinical course in female AC patients.…”
Section: Introductionmentioning
confidence: 99%
“…Though ARVC/D is a potentially life threatening disease, it may be managed conservatively even during pregnancy or with beta-blocker or sometime with implantable cardioverter-defibrillator who are at high risk, and one study revealed that approximately 13% and 5% were complicated by ventricular arrhythmias and heart failure, respectively [ 24 ].…”
Section: Discussionmentioning
confidence: 99%